2020
DOI: 10.1371/journal.pone.0230253
|View full text |Cite
|
Sign up to set email alerts
|

Comparing genome-scale DNA methylation and CNV marks between adult human cultured ITGA6+ testicular cells and seminomas to assess in vitro genomic stability

Abstract: Autologous transplantation of spermatogonial stem cells is a promising new avenue to restore fertility in infertile recipients. Expansion of the initial spermatogonial stem cell pool through cell culturing is a necessary step to obtain enough cells for effective repopulation of the testis after transplantation. Since in vitro propagation can lead to (epi-)genetic mutations and possibly malignant transformation of the starting cell population, we set out to investigate genome-wide DNA methylation status in uncu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 73 publications
2
13
0
Order By: Relevance
“…The chosen time points reflect distinct morphological changes of the PTC culture. During culture, we observed a notable transition from mostly floating, round cells at the onset of culture to a pronounced monolayer of attached spindle-shaped cells from day 13 onwards, with a smaller population of round germ cells adhering to the monolayer (Figure 1A, Video S1), consistent with previous studies that have reported similar transitions [21,22,29,35]. Throughout culture, PTCs were enriched for SSCs through MACS sorting for ITGA6+ cells, resulting in SSC-enriched PTC fractions (hereafter termed ITGA6 + PTC) obtained at six culture time points from four unique testicular tissue donors (total of 24 fractions) (Figure 1B).…”
Section: Derivation Of Itga6+ Testicular Cell Fractions From Mixed Testicular Cell Culturessupporting
confidence: 90%
See 2 more Smart Citations
“…The chosen time points reflect distinct morphological changes of the PTC culture. During culture, we observed a notable transition from mostly floating, round cells at the onset of culture to a pronounced monolayer of attached spindle-shaped cells from day 13 onwards, with a smaller population of round germ cells adhering to the monolayer (Figure 1A, Video S1), consistent with previous studies that have reported similar transitions [21,22,29,35]. Throughout culture, PTCs were enriched for SSCs through MACS sorting for ITGA6+ cells, resulting in SSC-enriched PTC fractions (hereafter termed ITGA6 + PTC) obtained at six culture time points from four unique testicular tissue donors (total of 24 fractions) (Figure 1B).…”
Section: Derivation Of Itga6+ Testicular Cell Fractions From Mixed Testicular Cell Culturessupporting
confidence: 90%
“…In that study, the expression of PDGFRA1 is shown from stem Leydig cells to adult Leydig cells including the perivascular and peritubular cell layers in the human testis. EMT has also been associated with risk of tumor formation, but in a recent study using the same culture procedure no changes in DNA methylation, indicative of tumorigenesis, were observed [ 35 ]. In addition, in an allogenic transplantation study using mouse in vitro propagated spermatogonia where the exact same culture medium was used as in our current study, no increased risk of cancer was reported in long-term followed transplanted mice compared to control [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strujik et al investigated CNVs in SE and reported that no CNV hotspot in SE was detected [ 37 ]. However, we detected CNV gain of all analysed genes in SE tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The main concern is that in vitro manipulation could affect the (epi-) genetic integrity of these cells and induce a carcinogenic phenotype or adverse health effects on the offspring. Throughout the years, several research groups have investigated possible chromosomal aberrations [18,19], and genetic or epigenetic instability of the SSC cultures in animal studies [18,[20][21][22] and human in vitro models [19,23]. Overall, the chromosomal integrity was conserved [18,19,23] as well as genomic stability [19,22].…”
Section: Genomic Stability Of Sscs In Culturementioning
confidence: 99%